PEMBERDAYAAN UMKM DION PET SHOP MELALUI IMPLEMENTASI DIGITAL MARKETING DAN TEKNOLOGI USAHA DI KOTA DEPOK - Nora Listiana; Marshada Marshada; Nike Nopitasari; Wita Arunita (FKIP Universitas Citra Bangsa, 2026)
This Community Service program aims to improve the competitiveness of the Dion Pet Shop MSME through the application of digital marketing and business technology. The program utilizes training and mentoring methods, including the use of social media, e-commerce platforms, and the implementation of the QRIS digital payment system. The results demonstrate an increase in partners' understanding and skills in managing digital marketing, expanding market reach, and improving transaction and operational efficiency. This program is expected to encourage sustainable digital transformation of MSMEs and serve as a model of empowerment for similar businesses.